Pengembangan Bahan Ajar IPS Model Shared Kelas VIII - Aziz Aziz; Pargito Pargito; Risma M Sinaga (Faculty of Teacher Training and Education, University of Lampung, 2017)
This study aims to develop teaching materials of social studies use model Shared class VIII SMP with the theme